MICROBIAL CONTAMINATION TEST USING THE MOST PROBABLE NUMBER (MPN) METHOD ON SWEET SOY SAUCE AROUND UPN “VETERAN” JAKARTA PONDOK LABU CAMPUS MICROBIAL CONTAMINATION TEST USING THE MOST PROBABLE NUMBER (MPN) METHOD ON SWEET SOY SAUCE AROUND UPN “VETERAN” JAKARTA PONDOK LABU CAMPUS - Ariska Deffy Anggarany; Alisha Dian Prasasti; Amara Ayu Karlina; Anisa Puja Ningrum; Aurelie Reginia Iteh; Bimo Asrul Seno; Nabilah Siti Zahara (Pharmacy Program, Faculty of Medicine, UPN Veteran Jakarta, 2024)
Sweet soy sauce is a fermented soybean product widely used as a traditional Indonesian seasoning. Its production process involves specific microorganisms to develop unique taste, aroma, and texture characteristics. However, poor hygiene and sanitation can lead to microbial contamination, such as Coliform, which may degrade quality and pose health risks. This study aimed to evaluate the microbiological quality of sweet soy sauce using the Most Probable Number (MPN) method. Samples were collected from food vendors around the UPN